The direct and indirect effects of the price of electricity on the production cost - Vallianatos, Charalampos (SPOUDAI Journal of Economics and Business, 2009)
In this paper we attempt to estimate the direct and indirect effects upon the production cost of various products of an exogenously determined change in the price of electricity. Electricity is a basic intermediate input for the production of all products. An exogenous increase in its price will, therefore, have two distinct effects upon the production cost of a certain product: a direct one, due to the increase in the price of electricity and an indirect one though the increase in the price of other inputs necessary for the production of this products (assuming that the increase in electricity can be transferred to products prices). This latter affect will depend on the volume of electricity consumed by each sector. In order to accomplish that the prices of the products of various sectors are expressed as linear functions of the price of electricity according to the Input – Output Table of the Greek Economy. The various sectors of the Greek Economy are classified according to the direct and indirect affect of the change in the price of the electricity.